Hubungan Peran Kader sebagai Jumantik dengan Perilaku Pencegahan Demam Berdarah Dengue (DBD) di Desa Pacul Tegal - Cyntia Tri Hardianti; Agus Budianto; Ikawati Setyaningrum; Imam Safi’i (Jurnal Sains dan Kesehatan, 2024)
Community behavior is the most important role to prevent and break the chain of DHF disease transmission by eradicating DHF mosquito larvae by conducting Mosquito Nest Eradication (PSN) activities through 3M Plus. The role of jumantik cadres is very important in changing people's behavior towards Mosquito Nest Eradication (PSN). The purpose of this study was to analyze the relationship between the role of jumantik cadres and dengue prevention behavior in Pacul Village, Talang Subdistrict, Tegal Regency. This type of research is descriptive correlation with cross sectional approach. The sample was 92 respondents using proportional simple random sampling technique. Data collection used a questionnaire of the role of the jumantik cadre and a questionnaire of Dengue Fever prevention behavior made by the researcher. Rank Spearman correlation test obtained a p value of 0.000 (P <0.05). Indicates that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant relationship between the role of jumantik cadres and dengue prevention behavior in Pacul Village, Talang Subdistrict, Tegal Regency.